OP42 Potential impacts of brexit on cardiovascular disease via changes to the price of fruits and vegetables: a modelling analysis. (September 2018) - Seferidi, S; Laverty, AA; Pearson-Stuttard, J; Guzman-Castillo, M; Collins, B; Capewell, S; O'Flaherty, M; Millett, C
Abstract : Background: The UK's decision to exit the European Union will likely affect its current trade regimes. Trade policy can alter food commodity availability and price; it is thus a potentially powerful determinant of food environments and subsequently health. The UK is highly dependent on its fruit and vegetable (F&V) imports. Brexit could therefore affect F&V price and consumption in the UK. Given the strong association between F&V intake and cardiovascular disease (CVD), our analysis aimed to quantify the potential effects of F&V price changes due to Brexit on CVD in English adults between 2020–2030. Methods: We used the previously validated IMPACT Food Policy Model. The model combined publicly available data on F&V trade, published estimates of UK-specific price elasticities, F&V intake data from the National Diet and Nutrition Survey, and coronary heart disease (CHD) mortality projections for 2020–2030. We estimated the number of CHD deaths and life-years lost between 2020–2030 among English adults aged 25 years and above as a consequence of five Brexit scenarios: (1) Transitional Brexit; (2) post-Brexit Free Trading Agreement with the EU and maintaining half of the non-EU free trade partners; (3) post-Brexit Free Trading Agreement with the EU but no trade deal with any non-EU countries; (4) post-Brexit liberalised trade regime; (5) no deal Brexit. We then performed Monte-Carlo simulations to better estimate uncertainty of inputs. Results: Under all Brexit scenarios, prices of F&V are likely to increase on average between 1.8% and 7.8%. The banana, citrus fruit, and tomato markets are likely to be the most disrupted, with price increases up to approximately 16.7%, 14.3%, and 13.4% respectively. A transitional Brexit is likely to result in approximately 670 (95% Uncertainty Interval: 430–980) extra CHD deaths and 6370 (4, 360–8, 990) life-years lost. A liberalised regime which eliminates all import tariffs is likely to contribute approximately 940 (600–1, 370) additional CHD deaths and 8870 (6, 060–12, 540) life-years lost, due to non-tariff trade barriers between the UK and the EU. A no-deal Brexit scenario might be the most harmful, generating approximately 2900 (1, 820–4, 310) extra CHD deaths and 27 440 (18, 200–39, 630) life-years lost between 2020–2030. Conclusion: This analysis suggested that under all modelled scenarios Brexit is likely to increase the price of F&V and thus have a detrimental effect on the future diet and health of English adults. The UK government should therefore aim to secure a post-Brexit food system that incentivises the UK population to purchase and consume healthy foods.